If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12c + -6c + 4 = 0 Reorder the terms: 4 + 12c + -6c = 0 Combine like terms: 12c + -6c = 6c 4 + 6c = 0 Solving 4 + 6c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 6c = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 6c = 0 + -4 6c = 0 + -4 Combine like terms: 0 + -4 = -4 6c = -4 Divide each side by '6'. c = -0.6666666667 Simplifying c = -0.6666666667
| 3n^2=-5-8n | | 9(0)-3y=9 | | 3m+4.25=26.75 | | 14x^2+8x-6=0 | | 6n+8=(12n+16) | | -10-10n=-8n | | -3(8r-2)=198 | | b-27=-84 | | q*6=4 | | 7x+17-6x=-5+(-13) | | 24u^3+1029=0 | | B^2=25/64 | | -500a^3-108=0 | | 5log(4x+8)-6=9 | | 1.1=4y+19.9 | | 2-7r=-7-6r | | 5=c/-4=7 | | 4x+2x+2=17 | | 11a+6-4a= | | 42+Y+X=42+X+Y | | 4(w-5)=5 | | 9a+6=12 | | 5m+3m=54-2m | | -18=6v+7v-16 | | -6x+7-7=-7x+2 | | -9-3u=7-u | | -3w+(-18)=0 | | 2x-39=11 | | 14x^2+179x-39=0 | | 10w-8w+14w= | | -23+7x=9(2x-3) | | 4.5+1.2p=6.1 |